The bonds of humanity : Cicero's legacies in European social and political thought, ca. 1100-ca. 1550 - Nederman, Cary J. (University Park, Pennsylvania : The Pennsylvania State University Press, 2020)
"Surveys the many different impacts of Ciceronian theories on a diverse array of texts and authors between 1100 and 1550, presenting a counternarrative to the widely accepted belief in the dominance of Aristotelianism in early European political and social thought"--
Introduction : Ciceronian ideas in early European social and political thought -- Prelude to the early European Cicero(s) -- Words and deeds : some twelfth-century Ciceros -- John of Salisbury : self-proclaimed Ciceronian -- Cicero in the universities -- Ciceronian impulses in Marsiglio of Padua -- Cicero speaks French -- Ciceronian imperialism -- Cicero against empire : Bartolome de Las Casas.
Includes bibliographical references (pages 201-214) and indexes.
eBooks on EBSCOhost
Keywords: Cicero, Marcus Tullius -- Influence; Cicero, Marcus Tullius -- Influence; Cicero, Marcus Tullius; Ciceronianism; Social sciences -- Europe -- History; Political science -- Europe -- History; Cicéronianisme.; Sciences sociales -- Europe -- Histoire; HISTORY / Medieval; Ciceronianism; Influence (Literary, artistic, etc.); Political science; Social sciences; Europe; Electronic books; History